2019
DOI: 10.1001/jamaneurol.2018.4182
|View full text |Cite
|
Sign up to set email alerts
|

Validation of Altered Umbilical Cord Blood MicroRNA Expression in Neonatal Hypoxic-Ischemic Encephalopathy

Abstract: IMPORTANCE Neonatal hypoxic-ischemic encephalopathy (HIE) remains a significant cause of neurologic disability. Identifying infants suitable for therapeutic hypothermia (TH) within a narrow therapeutic time is difficult. No single robust biochemical marker is available to clinicians. OBJECTIVE To assess the ability of a panel of candidate microRNA (miRNA) to evaluate the development and severity of encephalopathy following perinatal asphyxia (PA). DESIGN, SETTING, AND PARTICIPANTS This validation study include… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
27
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 49 publications
(30 citation statements)
references
References 52 publications
3
27
0
Order By: Relevance
“…In the model of perinatal asphyxia used in our study, hypoxia/ischemia increased the expression of miR-181b, which is known to activate caspase-3-dependent apoptotic pathways and to inhibit the prosurvival PI3K/Akt signaling pathway [37]. This is in line with a report by O'Sullivan et al [38], who showed upregulation of miR-181b in umbilical cord blood of newborns suffering from perinatal asphyxia. Therefore, targeting miR-181b could be a protective strategy against ischemic insult, as evidenced by the application of an antagomir [39,40].…”
Section: Discussionsupporting
confidence: 92%
“…In the model of perinatal asphyxia used in our study, hypoxia/ischemia increased the expression of miR-181b, which is known to activate caspase-3-dependent apoptotic pathways and to inhibit the prosurvival PI3K/Akt signaling pathway [37]. This is in line with a report by O'Sullivan et al [38], who showed upregulation of miR-181b in umbilical cord blood of newborns suffering from perinatal asphyxia. Therefore, targeting miR-181b could be a protective strategy against ischemic insult, as evidenced by the application of an antagomir [39,40].…”
Section: Discussionsupporting
confidence: 92%
“…We consider miR-374a to be another promising bridging biomarker candidate for neonatal HIE, when considering this study alongside previous studies in umbilical cord blood of HIE neonates by our group and others [ 5 , 51 , 56 ]. It may be particularly useful in identification of moderate-severe cases.…”
Section: Discussionmentioning
confidence: 88%
“…The role of miRNAs has been also reported in the context of neonatal diagnostics and the first description of miRNA profiling in UCB was reported in 2015 [29]. Recent studies have clearly shown that pathologies developing as a result of ischemia or asphyxia may alter the specific miRNA levels in UCB, suggesting their potential role in the early detection of such disorders [29,30]. PBMCs circulating in UCB might be a suitable alternative and valuable source of molecular biomarkers for neonatal diagnostics, thanks to the noninvasive and painless UCB collection at the time of child delivery.…”
Section: Introductionmentioning
confidence: 94%